ANALISIS KALIMAT PERSUASIF PADA IKLAN PRODUK G2G OLEH INFLUENCER MAHARAJASP DI MEDIA SOSIAL TIKTOK - Selvi Aulia Futri; Nisa Arianti Sri Lestari; Robi Abdul Rohim; Irfa Rufaidah; Iis Lisnawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This article discusses the development of TikTok as a major platform in digital marketing strategies, especially in Indonesia. TikTok is not only used for creativity, but also as an effective business medium in reaching young audiences through persuasive and creative content. Features such as the